1 Simplify \sqrt{{x}^{2}}
x
2
to xx.
y=(x-1)x+2x+2
y=(x−1)x+2x+2
2 Regroup terms.
y=x(x-1)+2x+2
y=x(x−1)+2x+2
3 Expand.
y={x}^{2}-x+2x+2
y=x
2
−x+2x+2
4 Simplify {x}^{2}-x+2x+2x
2
−x+2x+2 to {x}^{2}+x+2x
2
+x+2.
y={x}^{2}+x+2
y=x
2
+x+2
5 Move all terms to one side.
y-{x}^{2}-x-2=0
y−x
2
−x−2=0
6 Use the Quadratic Formula.
x=\frac{1+\sqrt{4y-7}}{-2},\frac{1-\sqrt{4y-7}}{-2}
x=
−2
1+
4y−7
,
−2
1−
4y−7
7 Simplify solutions.
x=-\frac{1+\sqrt{4y-7}}{2},-\frac{1-\sqrt{4y-7}}{2}
x=−
2
1+
4y−7
,−
2
1−
4y−7
Done